Emotional flexibility among university students - Akram, Maryam Ayham; Musa, Wathiq Omar (Journal of Tikrit University for Humanities, 2025)
The current research aims to identify the level of emotional flexibility among a sample of university students, as well as to find differences indicative of the variable according to gender and specialization on the sample consisting of (300) male and female students. The sample was distributed proportionately according to the variables of gender and academic specialization. The researcher prepared a scale to measure emotional flexibility and after presenting it to a committee of experts it was appointed to determine the validity of the items in measuring what it was designed to measure, and the researcher reached the following results: 1.University students have a high level of emotional flexibility. 2.There is no statistically significant difference in emotional flexibility according to the gender variable. 3.There is a statistically significant difference in mental motivation depending on the academic specialization variable, in favor of the humanities specializations.